EVALUASI IMPLEMENTASI PROGRAM PENDEKAR (PENDERES BADEG DESA KARANGSARI) MENGGUNAKAN METODE SOCIAL RETURN ON INVESTMENT (SROI) - Retno Suryani; Fatma Ziadati Husna; Afifah Munfaridah; Nurani Ikhlas (LPPM Universitas Bina Bangsa, 2022)
PT Pertamina (Persero) Fuel Terminal Maos conducted a community empowerment program in Karangsari Village, Cilacap Regency, Central Java Province. This program is called PENDEKAR (Penderes Badeg Karangsari) which has been implemented since 2020. This program aims to increase the productivity and income of sugar farmers in Karangsari Village by processing coconut sap water into export-worthy ant sugar and healthy organic sugar which has a good quality and has a high resale value. This program implies an economic and environmental impact on the surrounding community and PT Pertamina (Persero) Fuel Terminal Maos. This paper describes the results of the program using the evaluative type of social return on investment (SROI) method to evaluate, measure, and calculate the impact of the PENDEKAR (Penderes Badeg Karangsari) program that has been implemented. The result shows that the PENDEKAR Community Empowerment Program have an SROI value of 2.34. This concludes that the PENDEKAR program (Penderes Badeg Karangsari) is a good program and deserves to be implemented and developed in Karangsari village and even in other areas